2020
DOI: 10.51791/njap.v44i4.514
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility and growth performance of cockerels fed processed sickle pod (Senna obtusifolia) seed meal based-diets

Abstract:  A Feeding trial was conducted for sixteen weeks to evaluate nutrient utilization and growth performanceofcockerelsfedprocessedSennaobtusifoliamealbased-diets.Sixexperimental diets werecompounded tocontain 0%and20%eachoftheraw,boiled, soaked, sproutedand fermented Senna obtusifolia seed meal designated T1, T2, T3, T4, T5 and T6, respectively. Data were collected on nutrient digestibility, feed intake, weight gain, feed conversion ratio and mortality. Poor nutrient digestibility for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…(2016) also reported significant reduction of phytate, oxalate, saponins and tannin in S. obtusifolia seed boiled at 100°C for 40 min. Augustine et al (2017d) soaked the seed for 6, 12 and 24 h and found a 52% reduction in tannin content after 6 h. Increasing the duration of soaking above 6 h did not further reduce tannin content but phytate, oxalate and saponins reduced with increasing soaking duration up to 24 h. This suggests the presence of both condensed and hydrolysable tannins in S. obtusifolia seed. These authors however, observed significant reduction in the crude protein above 6 h and most essential amino acids above 12 h soaking, probably due to leaching.…”
Section: Effect Of Selected Processing Methods On Antinutritional Factor Content In Senna Productsmentioning
confidence: 94%
See 1 more Smart Citation
“…(2016) also reported significant reduction of phytate, oxalate, saponins and tannin in S. obtusifolia seed boiled at 100°C for 40 min. Augustine et al (2017d) soaked the seed for 6, 12 and 24 h and found a 52% reduction in tannin content after 6 h. Increasing the duration of soaking above 6 h did not further reduce tannin content but phytate, oxalate and saponins reduced with increasing soaking duration up to 24 h. This suggests the presence of both condensed and hydrolysable tannins in S. obtusifolia seed. These authors however, observed significant reduction in the crude protein above 6 h and most essential amino acids above 12 h soaking, probably due to leaching.…”
Section: Effect Of Selected Processing Methods On Antinutritional Factor Content In Senna Productsmentioning
confidence: 94%
“…The increased ALT, AST and ALP may suggest a liver dysfunction probably due to toxicity of the raw seed. Augustine et al (2018c) reported depressed weight gain, feed conversion ratio ( FCR ), and nutrient digestibility in broiler chickens fed 50 g raw S. obtusifolia seed meal/kg diet. The adverse effects of residual ANFs in the seed as earlier reported ( Savage, 2003 ; Amarowicz, 2007 ; Tapiwa, 2019 ) could be possible reasons for elevation of the serum indices.…”
Section: Effects Of Senna Seed Meal On Poultry Performancementioning
confidence: 99%